COST-BENEFIT ANALYSIS OF TRANSITION TO ELECTRIC VEHICLES IN A LOGISTICS COMPANY - Mihaela STET (Carpathian Journal of Electrical Engineering)
This research investigates the economic feasibility of transitioning a logistics company’s fleet to electric vehicles (EVs). The study evaluates the economic viability of this transition by comparing the total cost of ownership (TCO) of EVs to that of traditional internal combustion engine (ICE) vehicles. Key factors considered in the analysis include vehicle purchase costs, operational expenses, energy consumption and costs, maintenance expenses, and government incentives. The study aims to quantify the potential financial benefits and drawbacks associated with EV adoption and to assess the overall economic viability of such a transition. The findings of this CBA provide valuable insights for logistics companies seeking to make informed decisions about their fleet electrification strategies.